Case Report: Diagnosing and treating gallbladder neuroendocrine neoplasms through comparative analysis: a case series and literature review - Zhang, Jiayao; Li, Jiandong; Dong, Yuxing; Lu, Baochun (Frontiers in Oncology, 2025)
BackgroundGallbladder neuroendocrine neoplasms (GB-NENs) are exceedingly rare in clinical practice. To date, no large-scale, multicenter prospective studies have been conducted on this disease, resulting in a lack of established diagnostic and therapeutic experience or consensus. This case series reports seven GB-NEN patients who underwent different treatment modalities with varying outcomes. By integrating our institutional experience with previous literature, we aim to provide some therapeutic recommendations for GB-NEN patients.MethodsThe clinicopathological data of seven GB-NEN patients treated at our institution between June 2013 and June 2024 were retrospectively analyzed, with a focus on their treatment courses.ResultsSeven GB-NEN patients did not exhibite specific clinical manifestations or distinctive imaging features. All patients underwent surgical intervention, including radical resection in four cases. The overall survival ranged from 3 to 55 months, with a median survival of 19 months.ConclusionGB-NENs are highly aggressive and associated with poor prognosis. We recommend: 1) Radical cholecystectomy as the primary treatment for resectable GB-NENs; 2) Platinum-based chemotherapy as the first-line regimen, with close monitoring for drug resistance; 3) Early assessment of chemosensitivity to guide further treatment decisions, postoperative chemotherapy combined with adjuvant therapies may improve surgical efficacy.